1989
DOI: 10.1172/jci113953
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of experimental autoimmune diseases and prolongation of allograft survival by treatment of animals with low doses of heparins.

Abstract: The ability of activated T lymphocytes to penetrate the extracellular matrix and migrate to target tissues was found to be related to expression of a heparanase enzyme

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
127
1
2

Year Published

1990
1990
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(132 citation statements)
references
References 20 publications
2
127
1
2
Order By: Relevance
“…To induce AA, 9-to 10-wk-old Lewis rats (seven per group) were inoculated intradermally at the base of the tail with 0.1 ml of CFA containing 10 mg/ml Mycobacterium tuberculosis (H37RA; Difco), as previously described (17). DSF (300 g/rat per application) or water as control was administered p.o.…”
Section: Aa Assaymentioning
confidence: 99%
“…To induce AA, 9-to 10-wk-old Lewis rats (seven per group) were inoculated intradermally at the base of the tail with 0.1 ml of CFA containing 10 mg/ml Mycobacterium tuberculosis (H37RA; Difco), as previously described (17). DSF (300 g/rat per application) or water as control was administered p.o.…”
Section: Aa Assaymentioning
confidence: 99%
“…Indeed, previous studies have suggested a role for heparanase in various pathophysiological conditions, including tumor metastasis (Escobar Galvis et al, 2007;Vlodavsky and Friedmann, 2001), experimental autoimmune disease (Lider et al, 1989), amyloidosis (Li et al, 2005) and delayed type hypersensitivity (DTH) reactions . A role for heparanase in tumour metastasis is supported by the strong correlation between levels of heparanase expression and metastatic potential of B16 melanoma (Vlodavsky et al, 1999) and T lymphoma (Goldshmidt et al, 2002b) cells.…”
Section: Introductionmentioning
confidence: 99%
“…The closely related molecule heparan sulphate is, however, found on vascular endothelial cells, where it is considered to play a role in preventing non-speci®c adhesion of blood elements since it is now known that certain in¯ammatory cells, most notably lymphocytes, release heparan-degrading enzymes in order to aid their extravasation (reviewed by Vlodavsky et al, 1992) and that these enzymes are inhibited by heparin (Bar-Ner et al, 1987). Indeed, the inhibitory e ects of administered heparin on lymphocyte orchestrated processes such as graft vs host reactions (Gorski et al, 1991;Lider et al, 1989), delayed type hypersensitivity reactions (Sy et al, 1983) and allergic encephalomyelitis (Lider et al, 1990;Willenborg & Parish, 1988) are thought to involve heparanase inhibition. However, there is also evidence that heparin can a ect the entry of lymphocytes to lymph nodes and Peyer's patches (Bellavia et al, 1980), having potential consequences with respect to the recirculation of these cells.…”
Section: Introductionmentioning
confidence: 99%